2022
DOI: 10.1039/d2qo00504b
|View full text |Cite
|
Sign up to set email alerts
|

A tandem reduction of primary amines, carbonyl compounds, CO2, and boranes catalyzed by in situ formed frustrated Lewis pairs

Abstract: 2-Aminothiazole in combination with a boranetrimethylamine complex displays efficient catalytic activity for four-component reductive methylation of primary amines, carbonyl compounds, boranes, and CO2 (1 atm) under metal-free conditions. A wide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…also explored the dehydrogenation of 2‐aminothiazole with borane to form an intramolecular FLP for CO 2 activation. This facilitated a four‐component reductive methylation involving primary amines, carbonyl compounds, boranes, and CO 2 (as shown in Scheme 4e) [43] . This methodology holds promise for synthesizing diverse drug derivatives and serves as a case study in utilizing N‐containing compounds and boranes for CO 2 activation and conversion, followed by subsequent tandem reactions.…”
Section: Homogeneous Flpmentioning
confidence: 99%
“…also explored the dehydrogenation of 2‐aminothiazole with borane to form an intramolecular FLP for CO 2 activation. This facilitated a four‐component reductive methylation involving primary amines, carbonyl compounds, boranes, and CO 2 (as shown in Scheme 4e) [43] . This methodology holds promise for synthesizing diverse drug derivatives and serves as a case study in utilizing N‐containing compounds and boranes for CO 2 activation and conversion, followed by subsequent tandem reactions.…”
Section: Homogeneous Flpmentioning
confidence: 99%
“…Tertiary amines are widely used as important intermediates in medicine, agrochemicals, preservatives, dyes, and surfactants [1–6] . Traditionally, they have been synthesized through the amination of alcohols and halohydrocarbons, or reductive methylation of primary amines [7, 8] . However, these procedures are usually associated with the use of flammable hydrogen or toxic formaldehyde as the reductant, corrosive hydrochloric acid as an intermediate, or pungent dimethylamine as the amine source, which seriously pollute the environment and significantly affect human health [9, 10] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Traditionally, they have been synthesized through the amination of alcohols and halohydrocarbons, or reductive methylation of primary amines. [7,8] However, these procedures are usually associated with the use of flammable hydrogen or toxic formaldehyde as the reductant, corrosive hydrochloric acid as an intermediate, or pungent dimeth-ylamine as the amine source, which seriously pollute the environment and significantly affect human health. [9,10] To overcome these problems, utilization of N,N-dimethylformamide (DMF) as the amine source, reductant and solvent for reductive amination of aldehydes to synthesize tertiary amines has attracted increasing attention, because such a synthetic strategy can reduce the use of harmful substrates and simplify product separation.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a sustainable, economical, and easy-to-handle procedure for CO 2 transformation, our group has investigated cheap and readily available organocatalysts for CO 2 activation under mild conditions. 9 Thus, 2-amino-6-picoline–borane 9 b and 2-aminothiazole–borane 9 c catalytic systems were developed for the reductive methylation of amines with CO 2 . In our previous study, we found that different borane–amine complexes exhibit different selectivities for the production of formylated or methylated amines.…”
mentioning
confidence: 99%